Phytogenic Feed Additives on the Growth Performance of Broilers - Borromeo, Prenjie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This This study evaluated the effects of phytogenic feed additives on the growth performance and economic efficiency of broiler chickens using papaya (Carica papaya), katuray (Sesbania grandiflora), and aratiles (Muntingia calabura) leaf meals as natural alternatives to commercial antibiotic growth promoters. The study employed an experimental research design using a Completely Randomized Design (CRD) involving 150 broiler chicks distributed into five treatments with three replications. The treatments consisted of home-mixed rations without leaf meal, home-mixed rations with commercial antibiotic, and home-mixed rations supplemented with 5% papaya, katuray, and aratiles leaf meals. Data gathered included body weight, weekly weight gain, feed intake, percentage growth rate, feed conversion ratio, feed conversion efficiency, mortality rate, carcass characteristics, and return above feed and chick cost. The results revealed that phytogenic feed additives did not significantly affect body weight, weight gain, feed intake, and growth rate of broiler chickens. However, broilers supplemented with papaya leaf meal consistently showed better numerical performance in terms of final body weight, feed conversion ratio, feed conversion efficiency, and profitability. The proximate analysis further showed that papaya, katuray, and aratiles leaf meals contained appreciable levels of crude protein, crude fiber, calcium, and phosphorus, indicating their potential as alternative feed ingredients in poultry diets. Lower mortality rates were also observed among broilers fed phytogenic additives, suggesting favorable growth and survivability responses during the feeding period. The study concluded that papaya leaf meal has the greatest potential as a natural alternative to commercial antibiotic growth promoters by improving nutrient utilization, feed efficiency, and economic return without negatively affecting broiler performance. The findings support Sustainable Development Goal (SDG) 2 on Zero Hunger through improved poultry productivity and SDG 12 on Responsible Consumption and Production through the utilization of locally available plant-based feed additives. The study also contributes to sustainable and antibiotic-free poultry production by promoting environmentally friendly, cost-effective, and sustainable feeding practices in broiler farming.